The second fifty : answers to the 7 big questions of midlife and beyond - Whitman, Debra B. (W. W. Norton & Co. Inc., 2024)
"As she approached her fiftieth birthday, Debra Whitman, a globally recognized expert on aging, wanted to delve deeper into why so many Americans struggled to live well as they aged. And she began to wonder what was in store for her own second fifty. Suddenly, the questions she'd been studying for years became personal: How long will I live? Will I be healthy? Will I lose my memory? How long will I work? Will I have enough money? Where will I live? How will I die? Americans are now living decades longer than previous generations. These added years offer exciting possibilities but also raise crucial questions. In her groundbreaking book, Whitman provides a roadmap for navigating, and celebrating, the second half of life. Drawing on compelling stories from her own family and people across the country, interviews with experts, and cutting-edge research, she shares insights on brain health, the contributions and concerns of an older workforce, caregiving, financing retirement, and more. Her findings are often surprising: Americans over fifty are a boon to--not a drain on--the economy. Dementia rates have actually been declining as more people achieve higher levels of education and adopt healthier lifestyles. And while we've long known that staying connected to others is critical to mental health, it turns out it is also linked to a stronger immune system, lower blood pressure, and a longer life. Whitman presents practical steps we can take to help create a better second fifty for ourselves. But we can't do it alone. Whitman also calls for urgently needed changes that would make it easier for every American to enjoy a vital and meaningful second half of life." --